NEED ANALYSIS OF ENGLISH LANGUAGE SKILLS FOR AUTOMOTIVE DEPARTMENT OF THE ELEVENTH GRADE STUDENTS AT SMKN 1 SESEAN - Nilma Taula'bi' (UKI TORAJA, 2016)
This research aims are to find out the students’ need priority of English language skillsfor automotive department of the eleventh grade students at SMKN 1 Sesean. Thisresearch employed descriptive qualitative method. The subjects of this research were theeleventh grade students of automotive department of SMKN 1 Sesean academic year2015/2016. The instrument used namely questionnaire. The result of the research revealedthat the students’ need priority of English language skill for automotive department of theeleventh grade students at SMKN 1 Sesean is speaking.